Dissemination of Information Via Literacy Podcasts In Library - Sholikah, Siti Faridatus; Juvitasari, Prisca Budi (Progam Studi Ilmu Perpustakaan UIN Sumatera Utara Medan, 2024)
In the current era, getting information is very easy with the support of updated information technology or new media. The existence of new media has given rise to various innovations, one of which is the dissemination of information. In information dissemination activities, the main thing that must be present is the media for dissemination and the events that are broadcast, for example podcasts. Currently, podcasts are very popular with Gen Z. Because of the large number of podcast fans, the Blitar Regency Library and Archives Service has also adopted this activity to become a new innovation in disseminating information in libraries. The aim of this research is to determine the dissemination of information through whispered literacy podcasts at the Blitar Regency Library and Archives Service and to determine the barriers to information dissemination at the Blitar Regency Library and Archives Service. This research uses a qualitative type of research using a phenomenological approach. Researchers collected data using observation, interview and documentation techniques. The data that has been obtained is then analyzed using Miles and Huberman analysis in the form of data collection, data reduction, data presentation, and drawing conclusions. The results of this research show that the whispered literacy podcast has a schedule once a week with a scheduled host and resource person. The target of this Podcast is from ages 13+ or Gen Z. The media used are Instagram, Facebook, YouTube and websites. The obstacles that occur in this podcast activity consist of internal obstacles in the form of a lack of human resources, time and funds, while external obstacles include the difficulty of adjusting time between agencies and resource persons.